Democratic Ideals and the Politicization of Nature - Garside, N. author. aut Link
XIII, 198 p.
Keywords: Democratic Ideals and the Politization of Nature introduces the feral citizen as a response to a perceived need to revitalize the disruptive, critical, and exploratory nature of democratic culture. By learning from the traditions of aimless walking and by embracing a consciously feral method of political engagement, radically-democratic citizens can prompt political moments that create conditions where the primacy of the political can be performed, realized and defended. Ultimately, this book seeks not to solve the problems and paradoxes of democracy but to assist in unleashing and celebrating them. Garside concludes that using the methodology of feral citizenship inspired by environmentalism and democratic articulation to reprioritize the political within the green public sphere, citizens can reclaim necessary (and welcome) tensions between representations of nature and political citizenship.